Effectiveness of an information booklet regarding home based management on knowledge of caregivers of children with thalassemia - Verma, Rupali; Kumari, Rina; Verma, Nishant; Charan, Anugrah (International Journal of Contemporary Pediatrics, 2020)
Background: Thalassemia is one of the most common inherited diseases worldwide. It is (mediterranean anemia, cooley’s anemia) inborn hemolytic anemia characterized by a drop in the synthesis of hemoglobin. It produces hypochromic microcytic anemia due to imperfect hemoglobinization of RBCs, hemolysis, and futile erythropoiesis. It is due to mutations on chromosome 11 which leads to the synthesis of abnormal or absent beta globin chains. Recently there has been increasing cases of thalassemia worldwide. Hence, current study was planned to assess the knowledge of caregivers regarding homebased management of children with thalassemia. Methods: We assessed caregivers’ knowledge regarding home-based management of children with thalassemia in thalassemia day care department of pediatric KGMU Lucknow, using a self structured questionnaire. Statistical analysis was performed using SPSS software version 24. Results: The level of knowledge regarding pretest and posttest mean scores is 9.50 and 14.17 respectively. Paired t test calculated value was -9.808 which was much higher than the table value at p<0.05 level of significance. Conclusions: The study concluded that information booklet teaching was effective in improving the knowledge level of caregivers of children with thalassemia. More studies need to be done with larger sample size to empower cargivers regarding thalassemia.